Lila Caimari y Diego Galeano (eds.), Policía y sociedad en la Argentina (siglos XIX y XX) - Jeremías Silva (Prismas)
Lila Caimari y Diego Galeano (eds.), Policía y sociedad en la Argentina (siglos XIX y XX)